2018
DOI: 10.1038/s41598-018-22745-4
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Small-Vessel Layer, Sattler’s Layer and Haller’s Layer Thicknesses: The Beijing Eye Study

Abstract: To study macular choroidal layer thickness, 3187 study participants from the population-based Beijing Eye Study underwent spectral-domain optical coherence tomography with enhanced depth imaging for thickness measurements of the macular small-vessel layer, including the choriocapillaris, medium-sized choroidal vessel layer (Sattler’s layer) and large choroidal vessel layer (Haller’s layer). In multivariate analysis, greater thickness of all three choroidal layers was associated (all P < 0.05) with higher preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 45 publications
6
61
0
1
Order By: Relevance
“…Thus, although the changes of 610 lm that we observed are modest when compared with the overall choroidal thickness, they are much more significant when compared with the reported thickness of the small-vessel sublayer (approximately 30 lm) or Sattler's layer (approximately 90 lm). 36 Although the degree of choroidal thinning induced by hyperopic defocus amounted to approximately 10 lm regardless of baseline SFCT or age, the degree of choroidal thickening induced by myopic defocus was weakly and inversely correlated with baseline SFCT. The degree of choroidal thickening appeared to be moderately correlated with age within the age range of our subjects.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, although the changes of 610 lm that we observed are modest when compared with the overall choroidal thickness, they are much more significant when compared with the reported thickness of the small-vessel sublayer (approximately 30 lm) or Sattler's layer (approximately 90 lm). 36 Although the degree of choroidal thinning induced by hyperopic defocus amounted to approximately 10 lm regardless of baseline SFCT or age, the degree of choroidal thickening induced by myopic defocus was weakly and inversely correlated with baseline SFCT. The degree of choroidal thickening appeared to be moderately correlated with age within the age range of our subjects.…”
Section: Discussionmentioning
confidence: 84%
“…These changes are relatively small compared with overall SFCT (2%-8%), but as with age changes, they may be restricted to a sublayer of the choroid. A recent study of healthy subjects (n ¼ 1992) from the Beijing Eye Study 36 found that the thickness of the subfoveal small-vessel layer (including the choriocapillaris) was 30.5 6 9.8 lm, whereas the thickness of the medium-and large-sized vessel layers (Sattler's and Haller's layers) were 91.6 6 39.0 lm and 155.2 6 65.7 lm, respectively. 36 The Beijing study subjects had characteristics (age 62.7 6 9.3 years; SFCT 277 6 102 lm) similar to the subjects in the present study (age 57.4 6 4.07 years; SFCT of experimental eyes 226 6 72 lm), suggesting that the thickness of the choroidal sublayers in our study would be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the choroidal thinning in axially elongating eyes led to a decrease in the thickness predominantly of the large-sized vessels (Haller's layer) and medium-sized vessels (Sattler's layer) so that the ratio of the small-sized vessel layer to the total choroidal thickness increased with longer axial length. 23 In addition, axial elongation leads to thinning or compression of the intervascular tissue of the choroid. Thus, which of these axial elongation-related changes in the choroid leads to better visibility of the large choroidal vessels upon ophthalmoscopy, that is an increased degree of fundus tessellation, has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…반면 Chung et al [9]은 신경절세포-속얼기층(ganglion cell-inner plexiform layer)을 분 석하였으며, 반대안과 정상 대조군 사이의 유의한 차이가 없다 고 보고하였다. 맥락막두께(choroidal thickness)를 측정을 통해 맥락막 변화를 살펴 본 결과 [10][11][12], 고혈압과 당뇨 같은 전신인 자가 맥락막두께를 증가시킬 수 있다고 보고하였으며 [13,14], 단 안 망막정맥폐쇄에서 망막허혈로 인하여 병변안에서 반대안에 비해 맥락막두께가 증가하는 것이 보고되었다 [10,12].…”
unclassified